The Influence of Science Phylosophy in Improving Learning Ethics - Rima Erviana; Neneng Nur; Kun Nurachadijat (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2021)
This article was created with the aim of knowing how far and how much influence the philosophy of science has on the ethics of learning among students or students who are currently studying. The reason for raising this case is considered very important because of the decline in ethics among educational units at the elementary, secondary, and even tertiary levels compared to educational units in the past. The method used in writing this article is study literature, the basis used in discussing the ethics of learning uses the basis of Islamic theory or ethics according to Islam. Then the guidelines for learning ethics use the Al-Qur'an and hadith as well as the perspective of scholars who observe education. Ethics is the philosophy of human action as a human (human action). In a philosophical perspective, ethics is a philosophical investigation of human obligations and human behavior in terms of the good and bad of this behavior. Ethics also has a very basic nature, namely critical nature. In general it can be said that ethics is a philosophy of human action as a human being. An action has ethical value if it is carried out by humans and within a humane framework. It is clear that ethics deals directly with human actions or behavior. This humane behavior is not a meaningless behavior, but one that pursues good values.